Nanobody-mediated neutralization reveals an achilles heel for norovirus - Koromyslova, Anna D.; Devant, Jessica; Kiliç, Turgay; Sabin, Charles; Malak, Virginie; Hansman, Grant S. (Journal of virology, 2020)
Human norovirus frequently causes outbreaks of acute gastroenteritis. Although discovered more than five decades ago, antiviral development has, until recently, been hampered by the lack of a reliable human norovirus cell culture system. Nevertheless, a lot of pathogenesis studies were accomplished using murine norovirus (MNV), which can be grown routinely in cell culture. In this study, we analyzed a sizeable library of nanobodies that were raised against the murine norovirus virion with the main purpose of developing nanobody-based inhibitors. We discovered two types of neutralizing nanobodies and analyzed the inhibition mechanisms using X-ray crystallography, cryo-electron microscopy (cryo-EM), and cell culture techniques. The first type bound on the top region of the protruding (P) domain. Interestingly, this nanobody binding region closely overlapped the MNV receptor-binding site and collectively shared numerous P domain-binding residues. In addition, we showed that these nanobodies competed with the soluble receptor, and this action blocked virion attachment to cultured cells. The second type bound at a dimeric interface on the lower side of the P dimer. We discovered that these nanobodies disrupted a structural change in the capsid associated with binding cofactors (i.e., metal cations/bile acid). Indeed, we found that capsids underwent major conformational changes following addition of Mg2+ or Ca2+. Ultimately, these nanobodies directly obstructed a structural modification reserved for a postreceptor attachment stage. Altogether, our new data show that nanobody-based inhibition could occur by blocking functional and structural capsid properties. - IMPORTANCE This research discovered and analyzed two different types of MNV-neutralizing nanobodies. The top-binding nanobodies sterically inhibited the receptor-binding site, whereas the dimeric-binding nanobodies interfered with a structural modification associated with cofactor binding. Moreover, we found that the capsid contained a number of vulnerable regions that were essential for viral replication. In fact, the capsid appeared to be organized in a state of flux, which could be important for cofactor/receptor-binding functions. Blocking these capsid-binding events with nanobodies directly inhibited essential capsid functions. Moreover, a number of MNV-specific nanobody binding epitopes were comparable to human norovirus-specific nanobody inhibitors. Therefore, this additional structural and inhibition information could be further exploited in the development of human norovirus antivirals.
Gesehen am 27.08.2020